Colloquial Emotive Lexicon of Russian in Aspect of Polyparadigmality: Lexicographic Perspective (Thesaurus Dictionary “Emotion Alphabet”) - L. G. Babenko; V. V. Danilova (Научный диалог)
The article is dedicated to the study of colloquial emotive lexicon of the Russian in the aspect of polyparadigmality. The peculiarities of its categorization, conceptualization, and interpretation are examined from the perspectives of various scientific approaches. The analysis of colloquial emotive lexicon in the Russian is conducted in comparison with a multitude of normative literary lexicon presented in the thesaurus dictionary ‘Emotion Alphabet.’ Together, they comprise 11,210 units of analysis, with 2,073 lexemes belonging to colloquial emotive lexicon. It is considered as a lexical-semantic space in a spatial dimension, with its internal structure constructed in a horizontal-vertical dimension at the intersection of lexical sets of colloquial emotive lexicon of different nature. The study employs a complex of linguistic methods, including statistical description, structuralsemantic, functional-semantic, denotativeideographic, linguistic-cognitive, and other methods of analysis. This allows for presenting colloquial emotive lexicon as an overlapping set of various groups of lexemes: denotative-ideographic, cognitive-derivational, semantic-functional, and functional-stylistic. Trends and cognitive strategies in the formation of this set are identified in comparison with literary language. The results of the study will be used in the future for creating a thesaurus dictionary of colloquial emotive lexicon.